2013
DOI: 10.1155/2013/901589
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Effectiveness in Chronic Myeloid Leukemia with Additional Cytogenetic Abnormalities at Diagnosis among Black Africans

Abstract: Imatinib mesylate provides good results in the treatment of CML in general. But what about the results of this treatment in CML associated with additional cytogenetic abnormalities at diagnosis among black Africans? For this, we retrospectively studied 27 cases of CML associated with additional cytogenetic abnormalities, diagnosed in the department of clinical hematology of the University Hospital of Yopougon in Côte d'Ivoire, from May 2005 to October 2011. The age of patients ranged from 13 to 68 years, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also, the study of Oyekunle et al, 29 , showed that the clinical phase of the disease at diagnosis and the hematocrit can be used to stratify patients into low, intermediate, and high risk groups, with significantly different survival outcomes in Nigerian patients with CML. Aissata et al, 17 , reported that CML patients were severely symptomatic with a performance status ≥2 in 100%, splenomegaly in 100%, fever in 74%, hepatomegaly in 48%, bone pains in 48% and lymphadenopathy in 22%. Splenomegaly was relatively large, ≥10cm in 74%, probably due to the long period of consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study of Oyekunle et al, 29 , showed that the clinical phase of the disease at diagnosis and the hematocrit can be used to stratify patients into low, intermediate, and high risk groups, with significantly different survival outcomes in Nigerian patients with CML. Aissata et al, 17 , reported that CML patients were severely symptomatic with a performance status ≥2 in 100%, splenomegaly in 100%, fever in 74%, hepatomegaly in 48%, bone pains in 48% and lymphadenopathy in 22%. Splenomegaly was relatively large, ≥10cm in 74%, probably due to the long period of consultation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Imatinib mesylate provides good results in the treatment of CML in general. 17 Imatinib mesylate, a selective inhibitor of BCR-ABL kinase activity, selectively inhibits downstream signaling and the growth of BCR-ABL+ cells, inducing apoptosis of these cells. 2,18 The development of the BCR-ABL-targeted Imatinib mesylate represents a paradigm shift in the treatment of CML.…”
Section: Introductionmentioning
confidence: 99%